Performing gender a mixed method analysis on the impact of Disney animated films on primary pupils' sex typing behavior - Fernando, Ivy Mae F. (2023)
The burgeoning literature regarding Disney animated films and their problematic and stereotypical portrayals of race, culture, color, and gender, among others have propelled the interest on studying the films media effects to their possible audiences, particularly children. Consequently, it is observable that Disney animated films are one among the many, if not widely consumed by Filipino audiences, and therefore Filipino children are argued to have been exposed on the stereotypical gender-related messages from the films. This is deemed to be alarming, especially that there is little to no study that examined how the exposure to Disney animated films affect Filipino children?s internalization of gender and gender role stereotypes and its impact on children's sex typing behavior. Thus, using a mixed method approach, the researcher sought to explore whether exposure to the gendered messages embedded in the Disney animated films creates an impact on Filipino children?s sex typing behavior, particularly on primary pupils studying at Mintal Elementary School. The study conducted a correlation between the primary pupils? exposure to Disney animated films and their sex typing behavior and it was found that the two variables do not have a statistically significant relationship. However, it was further inferred that the two variables relate with each other as they towards opposite or inverse directions, meaning that as their exposure to Disney animated films increases, their sex typing behavior tends to decrease. Moreover, the cognitive, behavioral, and environmental influences on a child?s sex typing behavior were also explored in the study, through Albert Bandura?s Social Cognitive Theory (1986). It was determined that the encoding and decoding of gender-related messages and the development of children?s sex typing behavior are greatly impacted by a continuous process of meaning-making which is officiated by the mentioned factors. The findings of the study further provided a baseline data, particularly in understanding the gender development of a Filipino children in relation to the influence of Disney animated media